1976
DOI: 10.1084/jem.144.2.456
|View full text |Cite
|
Sign up to set email alerts
|

T-Lymphocyte precursors. I. Synergy between precursor and mature T lymphocytes in the response to concanavalin A.

Abstract: When mouse bone marrow cells are mixed with cortisol-resistant thymocytes and stimulated in vitro with concanavalin A, the mitogenic response observed is much greater than additive, that is, it is synergistic. Between 94 and 96% of responding cells could be identified as T cells (Thy-1 positive) and of these, 79-100% derived from the cortisol-resistant thymocyte population, not from the bone marrow. Purified macrophages could not replace bone marrow; and marrow depleted of mature T or B cells worked as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1977
1977
1981
1981

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…TTie evidence that population I gives rise to population II (Miller et al 1977) is indirect, and the two cells may yet prove to have independent origins. Another possibility is that population I cells are non-© bearing prethymic stem cells (Komuro & Boyse 1973, Cohen & Fairchild 1976 which somehow aid in the activation of CLP.…”
Section: IImentioning
confidence: 99%
“…TTie evidence that population I gives rise to population II (Miller et al 1977) is indirect, and the two cells may yet prove to have independent origins. Another possibility is that population I cells are non-© bearing prethymic stem cells (Komuro & Boyse 1973, Cohen & Fairchild 1976 which somehow aid in the activation of CLP.…”
Section: IImentioning
confidence: 99%
“…14-16, 20, 27, 29, 31]. The helper cells have been characterized as macrophages [3,11,12,14,20,27,29], T cells [5,8,9] and B cells [3]. It has also been reported that low numbers of adherent cells can enhance the response to polyclonal T-cell activators, whereas higher numbers of adherent cells inhibit the T-cell response [10,18].…”
mentioning
confidence: 99%
“…They do, however, synergistically support the proliferation of a small number of mature T cells stimulated by Con A, as do pre-T cells [8] . One hundred thousand lymph node cells cultured alone gave a Con A response of 4,736 cpm; in the presence of 50,000 bone marrow cells this was 11,795 cpm, and in the presence of 50,000 colony cells, 16,892 cpm.…”
Section: : Jssmentioning
confidence: 98%
“…This synergistic interaction has been used as the basis of a T cell progenitor assay [8]. It was applied to pooled colony cells by mixing them with small numbers of syngeneic lymph node cells and assaying the increase in tritiated thymidine incorporation following Con A stimulation, as described elsewhere [8].…”
Section: Synergy Assay For Pre-t Cellsmentioning
confidence: 99%